Community Empowerment Through the Solid Organic Fertilizer Production Program as a Waste Management Effort to Support Sustainable Agriculture in Jember Regency - Rahayu, Puji; Maulida, Zulfa; Utami, Ratih Apri; Avivi, Sholeh; Hoesain, Mohammad (Universitas Mataram, 2024)
Jember Regency has potential in the agricultural sector with abundant biodiversity, as well as a community culture that respects nature. This potential has not been managed optimally due to various problems such as limited creativity and knowledge of farmers regarding production, access, and limited market opportunities. To overcome this problem, it is necessary to empower the community through technology transfer, one of which is the manufacture of solid organic fertilizer from local ingredients in Jember district. This activity is an effort made to create environmentally friendly agriculture and can reduce organic waste pollution, one of which is animal waste. The specific aim of carrying out this activity is so that farmers can process organic materials in the surrounding environment to make organic fertilizer, thereby reducing farmers' dependence on inorganic fertilizers. This training in making organic fertilizer can increase farmers' knowledge and skills in increasing soil fertility and increasing production using organic materials. Implementation methods include socialization or counseling and training.